Improving Watershed Management Programs - Gonzalez, Fernando; Smyle, James; Dalton, Johan; Kerr, John; Kiersch, Benjamin; Tucker, S P (Annals of Arid Zone, 2016)
Watersheds have become an integral component of natural resources management. It is an integrated approach to water management. The major issues and challenges involved in watershed management are identified and discussed here. At the higher slopes changes in land use tend to generate downstream effects that impact on other stakeholders in the watershed. Intact, both costs and benefits need to be equally shared amongst both upstream and downstream stakeholders. The watershed management incorporates improving management of (a) natural resources, (b) local development and (c) externalities. Improving management of externalties is crucial in watershed management because improving equity becomes a prerequisite to improving the efficiency and sustainability of watershed investments. Rural poverty and degradation of natural resources are interlinked